Information exchange through non-binding advance price announcements: An antitrust analysis - Willem Boshoff; Stefan Frübing; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We study the welfare effects of non-binding advance price announcements. Applying a differentiated Bertrand model with horizontal products and asymmetric information, we find that such announcements can help firms to gain information on each other thereby allowing them to achieve higher profits. However, our results also show that the overall welfare effects of such announcements in a context of heterogeneous products are not as clear-cut as previous research in a homogeneous products framework has suggested. We conclude that - although non-binding advance price announcements may raise competition concerns - in many settings, their positive effects are likely to outweigh the potential detrimental effects on welfare.
urn:nbn:de:bsz:180-madoc-397351
Keywords: L41; K21; 330; antitrust policy; collusion; information exchange; price announcements